The Legal Politics of Disaster Management Budgeting: A Case Study of Natural Disasters in Sumatra: Politik Hukum Anggaran Penanggulangan Bencana Alam: Studi Kasus Bencana Sumatera - Mubarok, Rizki; Tjandra, W. Riawan (Universitas Islam Indonesia, 2025)
The 2025–2026 State Budget (APBN) represents a critical juncture in Indonesia's disaster management budgeting politics, allocating The National Agency for Disaster Countermeasure (BNPB) budget to a fifteen-year low of only 0.013% of state expenditure. This reveals an ambivalent dynamic: while hydrometeorological risks in Sumatra escalate with estimated losses of IDR 51.82 trillion, the fiscal design reinforces disasters as mere contingency issues by minimizing preventive funding. This article analyzes the reconstruction of disaster budgeting politics within the 2025–2026 APBN, specifically regarding national disaster status determination, regional fiscal capacity, and citizens' constitutional right to safety. Employing a normative juridical method with statutory and case study approaches, this research examines the Disaster Management Law, APBN and Financial Notes Law, and Sumatra’s economic impact data. Findings indicate three primary trends: the marginalization of mitigation in routine spending, executive discretion in status determination driven by fiscal calculations and national reputation, and the lack of institutionalized ecological justice in budget planning. The study recommends that disaster budgeting must be reconstructed through risk-based budgeting, automatic fiscal thresholds for emergency status, and the integration of ecological risks into regional transfers. This ensures alignment with the principles of responsive and sustainable state financial law, providing a more robust framework for national disaster resilience and citizen protection.